Use of hydrogen peroxide and percarbonate to treat chlorinated aromatic hydrocarbon-contaminated soil - Viisimaa, Marika; Goi, Anna (Journal of Environmental Engineering and Landscape Management, 2014)
This study compared treatment methods that utilised a liquid carrier of hydrogen peroxide and a solid carrier, percarbonate, for p-dichlorobenzene, p-chloro-m-cresol and p-chlorothymol degradation in the soil. The targeted chlorinated aromatic contaminants in the soil degraded to a certain level when treated with the liquid hydrogen peroxide, but the removal efficacy was not dependent on the dosage. In contrast, an increase in the percarbonate dosage enhanced the contaminant removal. Supplementary ferrous iron was more effective for the treatment that employed the liquid carrier of hydrogen peroxide than the treatment employing the solid carrier. Although acidic pH conditions (initial pH of 2.5) favoured contaminant degradation using liquid hydrogen peroxide, the treatment involving percarbonate resulted in more effective contaminant removal without any soil pH preadjustment. Therefore, the solid carrier of hydrogen peroxide, percarbonate, was concluded to be an effective alternative to the liquid carrier, resulting in greater contaminant removal at natural soil pH values.